Performance analysis of DOCSIS standard 1.1 used in Hybrid Fiber-Coax (HFC) network / Hasrol Harun - Harun, Hasrol (2009)
Hybrid Fiber Coax (HFC) cable networks have been used in the past primarily to deliver broadcast-quality TV signals to homes. The wide availability of such systems and their extremely wide bandwidth allows extending their functionality to deliver high-speed broadband data signals to end-users. Data over Cable System Interface Specifications (DOCSIS), a MAC protocol elaborated under the leadership of Cable Television Laboratories, Inc., has been established as the major industry standard for two-way communications over HFC cable plants. This thesis develops the Performance Analysis of Cable Modem Network. A worldwide demand for high speed broadband across commercial and residential regions is emerging rapidly due to the increasing reliance on web for information, business, entertainment and new upcoming high bandwidth intensive or real-time applications. Cable modem is a highspeed data device that provides an environment for high-speed digital data access from the Internet over cable television. The cable modem typically has two main connections; one to the cable outlet on the wall and the other connection is to the computer (PC), which has 1,000 times faster in download and upload than the telephone modem connection. The speed of cable modem uploading is a little bit slower than the downloading speed. That makes it sure that the user spends less time waiting for information. The cable modem modulates the digital transmission of data into analog information (uploading) and then demodulates the analog transmission back into digital data (downloading). However, the cable modem translates the digital data into an analog form similar to the way that used in television. The most predominant connection of cable modem is through Ethernet 10Base T that the COM (communications) port on the computer.